Oil Price Shocks-Macro Economy Relationship in Turkey - Ozturk, Feride (Asian Economic and Financial Review, 2015)
This paper analyzes the impact of oil price shocks on the selected macroeconomic variables in Turkey for the period of 1990Q1-2011Q4. Vector Autoregression (VAR) models and bivariate Granger causality tests are applied to determine the oil price shocks - macro economy relationship. The empirical findings show that both symmetric and positive oil price shocks decrease industrial production, money supply, and imports while the negative oil price shocks increase imports. Granger causality analysis demonstrate that symmetric and positive oil price shocks Granger-cause industrial production and imports in Turkey.